Translation and validation of the Persian version of the perception to care in acute situations (PCAS-P) scale in novice nurses - Reza Nemati-Vakilabad; Maryam Khoshbakht-Pishkhani; Saman Maroufizadeh; Nazila Javadi-Pashaki (BMC Nursing, 2024)
Abstract Background Novice nurses providing care in acute conditions should have satisfactory performance. Accurate and appropriate evaluation of the performance of novice nurses in providing care in acute situations is essential for planning interventions to improve the quality of patient care. This study was conducted to translate and evaluate the psychometric properties of the Persian version of the Perception to Care in Acute Situations (PCAS-P) scale in novice nurses. Methods In this methodological study, 236 novice nurses were selected by the convenience sampling method. 17-item scale PCAS-P was translated into Persian by the forward-backward process. Then, this version was used for psychometric evaluation. For this purpose, face validity, content validity, and construct validity were assessed using confirmatory factor analysis. Internal consistency and stability reliability were calculated. The data were analyzed using SPSS and AMOS software. Results The PCAS-P scale maintained the meaning of the original English version and was clear, explicit, and understandable for novice nurses. Confirmatory factor analysis showed that this Persian version is consistent with the proposed model and confirmed the fit of the three-factor model. The values of Cronbach’s alpha coefficient, McDonald’s omega, Coefficient H, and average inter-item correlation were excellent for the overall scale and its dimensions, and the three latent factors had good convergent and discriminant validity. Additionally, the average measurement size was 0.944 ICC (95% CI 0.909 to 0.969). Conclusion The PCAS-P scale is valid and reliable for measuring novice nurses’ perception of acute situations.